Chrysanthemum cultivation: A remunerative business for meeting the domestic demand - Bala, Madhu; Singh, S K; Salhotra, Ritish (Indian Horticulture, 2025)
Chrysanthemum is a widely cultivated ornamental crop with high commercial and aesthetic value. Due to its diverse flower forms, colours, and adaptability, it serves multiple purposes as cut flowers, loose flowers, pot culture, garden decoration, and religious use. Its year-round production is feasible through photoperiod and varietal manipulation. The crop is highly remunerative, offeringsubstantial income through rooted cuttings, potted plants, and loose flowers. Cultural practices like pinching, disbudding, staking, and pest management ensure high-quality blooms. Chrysanthemum also supports value-added products such as garlands, bouquets, and floral ornaments. Its versatility and profitability make it a promising crop for commercial growers, hobbyists, and floriculture-basedenterprises in both open and protected cultivation systems.